CASH HOLDING PROBLEMS: GROWTH OPPORTUNITY, FINANCIAL RATIOS, FIRM SIZE OF BEI PROPERTY COMPANIES - Ferry Safriandi; Aria Masdiana P; Windy Aginta (RADJA PUBLIKA, 2026)
This study examines and analyzes the influence of growth opportunity, leverage, and firm size partially and simultaneously on cash holdings in property and real estate sector companies in 2022–2024. This research was conducted on property and real estate companies listed on the Indonesia Stock Exchange between 2022 and 2024. Data was obtained from the official Indonesia Stock Exchange website, www.idx.co.id. The population in this study was 92 property and real estate companies. Based on the criteria, 43 companies were selected as samples. The test results of Growth Opportunity (X1) have no effect on Cash Holding (Y) in Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange (IDX) in 2022-2024. The results of Financial Ratios (X2) and Firm Size have an effect on Cash Holding (Y) in Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange (IDX) in 2022-2024. The results of Simultaneous testing of Growth Opportunity, Financial Ratios and Firm Size have no effect on Cash Holding (Y) in Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange (IDX) in 2022-2024.